2014
DOI: 10.1016/j.placenta.2013.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Review: Placenta-specific microRNAs in exosomes – Good things come in nano-packages

Abstract: MicroRNAs (miRNAs) are small noncoding RNA gene products that commonly regulate mRNA expression by repression of translation and/or transcript decay. Whereas common and unique types of miRNAs are expressed by the placenta during pregnancy, the functions of most placental miRNA species are unknown. In addition to their intracellular silencing function, miRNAs are also released to the extracellular space and systemic circulation, where they can potentially target cells to regulate mRNA and protein expression, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
160
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(161 citation statements)
references
References 59 publications
0
160
0
1
Order By: Relevance
“…111 Exosomes containing the C19MC miRNA cluster infer viral resistance to recipient cells through autophagy, 113 and may help immunologically protect the developing fetus. These recent studies illustrate that exosomes may play an important role in maternal-fetal exchange, 111,114 as well as in embryo implantation through maternal-fetal cross-talk. 112 The most abundant miRNAs in placental exosomes are miR-17, miR-106a and miR-200c.…”
Section: Microrna Regulation In the Placentamentioning
confidence: 89%
“…111 Exosomes containing the C19MC miRNA cluster infer viral resistance to recipient cells through autophagy, 113 and may help immunologically protect the developing fetus. These recent studies illustrate that exosomes may play an important role in maternal-fetal exchange, 111,114 as well as in embryo implantation through maternal-fetal cross-talk. 112 The most abundant miRNAs in placental exosomes are miR-17, miR-106a and miR-200c.…”
Section: Microrna Regulation In the Placentamentioning
confidence: 89%
“…Therefore, changes in placental cholesterol uptake and transfer are more likely to affect the fetal brain via further impact on placental function. For example, impaired trophoblast uptake of cholesterol may disrupt maternal-fetal cross-talk by reducing substrates for steroidogenesis as well as for synthesis of cholesterolcontaining exosomes, non-hormonal communicators that regulate immune homeostasis (Beninson and Fleshner, 2014;Ouyang et al, 2014).…”
Section: Nutrient Exchange and Energy Homeostasismentioning
confidence: 99%
“…Accumulated evidence has proved that exosomes secreted by MSCs show promise in different tissue repair processes including reducing injury caused by myocardial ischemia-reperfusion (Lai et al, 2010), promoting neurological recovery from stroke (Xin et al, 2013), and promoting wound healing through improving skin cells survival (Zhang et al, 2014). A few studies have also demonstrated that the underlying mechanism of these effects is most likely acting through miRNAs (Hulsmans and Holvoet, 2013;Ouyang et al, 2014). miRNAs are highly conserved noncoding RNAs (18-24 nucleotides) that regulate target gene expression by mediating mRNA degradation or translational inhibition (Carthew and Sontheimer, 2009).…”
Section: Introductionmentioning
confidence: 99%